In situ crosslinked smart polypeptide nanoparticles for multistage responsive tumor-targeted drug delivery. Issue 11 (29th February 2016) - Yi, Huqiang; Liu, Peng; Sheng, Nan; Gong, Ping; Ma, Yifan; Cai, Lintao
Abstract : We synthesized a smart polypeptide copolymer based on n -butylamine-poly(l -lysine)- b -poly(l -cysteine) with functionalization of folic acid and 1, 2-dicarboxylic-cyclohexene anhydride for multistage responsive tumor-targeted drug delivery. Abstract : Smart tumor-targeted drug delivery is crucial for improving the effect of chemotherapy and reducing the adverse effects. Here, we synthesized a smart polypeptide copolymer based on n -butylamine-poly(l -lysine)- b -poly(l -cysteine) (PLL-PLC) with functionalization of folic acid (FA) and 1, 2-dicarboxylic-cyclohexene anhydride (DCA) for multistage responsive tumor-targeted drug delivery. The copolymers (FA-PLL(DCA)-PLC) spontaneously crosslinked in situ to form redox and pH dual responsive FA-PLL(DCA)-PLC nanoparticles (FD-NPs), which had a reversible zeta potential around −30 mV at pH 7.4, but switched to +15 mV at pH 5.0. Moreover, FD-NPs effectively loaded DOX with a loading capacity at 15.7 wt%. At pH 7.4, only 24.5% DOX was released within 60 h. However, at pH 5.0, the presence of 10 mM DTT dramatically accelerated DOX release with over 90% of DOX released within 10 h. Although the FD-NPs only enhanced DOX uptake in FA receptor positive (FR + ) cancer cells at pH 7.4, a weak acidic condition promoted FD-NP-facilitated DOX uptake in both FR + HeLa and FR − A549 cells, as well as significantly improving cellular binding and end/lysosomal escape. In vivo studies in a HeLa cancer model demonstrated that the charge-reversible FD-NPs delivered DOX into tumors more effectively than charge-irreversible nanoparticles. Hence, these multistage responsive FD-NPs would serve as highly efficient drug vectors for targeted cancer chemotherapy.